An Analysis Of Affirmative Action Across The Globe (International Journal of Food and Nutritional Sciences, 2022)
Affirmative action across the world Several countries, including the United States and India, have implemented affirmative action policies to combat discriminatory practices against historically oppressed groups. In the United States, affirmative action is described as a system of preferential treatment for minorities and women, aiming to address the opportunities denied to them due to past and ongoing discrimination. Interestingly, India adopted affirmative action well before the United States, primarily to address the disadvantaged segments of its population, particularly groups like the "untouchables" who occupy the lowest tier of the Hindu caste system. Indian affirmative action is often referred to as "compensatory discrimination," a term used by legal scholars like Parmanand Singh and Marc Galanter.